Nierozstrzygalność - drugie imię dekonstrukcji? - Winiecka, Elżbieta (Wydawnictwo Naukowe UAM, 2003)
The article focuses on the problem of undecidability - the main feature of literature according to Derrida. Numerous examples of undecidability shows that it is not deconstruction which has found this kind of reading. For structuralists undecidability was a feature of poetry. Derrida broadens this onto all literary texts. Cancelling oposition between 'inside' and 'outside' he liquidates all natural for work contests: historical, sociological etc., and reduces literary text to the endless re-interpretation. It makes literary sigificants insignificant for culture and human being. Exploration of the margins of the literary texts thwarts hierarchy of importancy and opens the door for different kinds of abuses. This is why the author argues with Derrida's thesis and guards traditional role of the autor, reader and literature.
Undecidability - the second name of deconstruction?